MIRROR THERAPY CAN IMPROVE MUSCLE STRENGTH IN NON-HEMORRHAGIC STROKE PATIENTS - widiyono widiyono; Vitri Dyah Herawati; Wiwik Nurani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Stroke patients experience haemiparesis (muscle weakness on one side of the body). Stroke management is done by pharmacological and non-pharmacological means. Pharmacologically, stroke management can be given fibrinolytics, while non-pharmacologically, exercises such as mirror therapy can be done. Objective: to determine the effect of mirror therapy can increase muscle strength in patients with non-hemorrhagic stroke. Methods: The type of research used is pre-experiment design without control group. The intervention given is the provision of mirror therapy for a duration of 15 minutes 6 times a week. The research was conducted in all internal medicine inpatient rooms at Kustati Islamic General Hospital Surakarta. The population of this study were all non-hemorrhagic stroke patients. This study used purposive sampling technique obtained as many as 35 patients. The instruments used to measure muscle strength are MMT (Manual Muscle Testing) observation sheets and mirror therapy SOPs. The data analysis used was the Wilcoxon Signed Rank Test analysis test. Results: there is an effect of mirror therapy on muscle strength in non haemorrhagic stroke patients at Kustati Islamic General Hospital Surakarta with p-value = 0.001. Conclusion: Mirror Therapy can be used as one of the interventions that can be used by nurses in carrying out nursing care actions for stroke patients in increasing muscle strength.